Impact of bariatric surgery on serum urate targets in people with morbid obesity and diabetes: a prospective longitudinal study. Issue 5 (19th November 2013) - Dalbeth, Nicola; Chen, Peggy; White, Marie; Gamble, Gregory D; Barratt-Boyes, Caran; Gow, Peter J; Orr-Walker, Brandon
Abstract : Objectives: Weight loss leads to reduced serum urate (SU) in people with obesity. However, the clinical relevance of such reductions in SU is unknown. This study examined the impact of non-surgical weight loss and bariatric surgery on SU targets in people with morbid obesity and diabetes. Methods: The study was a single-centre, prospective study of 60 people with type 2 diabetes and body mass index ≥35 kg/m 2 . Following 6 months of non-surgical weight loss, all participants had laparoscopic sleeve gastrectomy, with a further 1 year of follow-up. Serial SUs were measured throughout the study. Results: Participants experienced mean (SD) weight loss of 5.5 (4.1) kg prior to surgery and 34.3 (11.1) kg following surgery. SU did not change following non-surgical weight loss (0.38 (0.09) mmol/L at baseline and 0.38 (0.10) mmol/L at follow-up), but increased to 0.44 (0.15) mmol/L in the immediate postoperative period and reduced to 0.30 (0.08) mmol/L 1 year after surgery (p<0.05 for both compared with baseline). Baseline SU, cessation of diuretics, female sex and change in creatinine independently predicted change in SU at the final visit. In participants without gout, SU above saturation levels (≥0.41 mmol/L) were present in 19/48 (40%) at baseline and 1/48 (2%) 1 year after surgery (p<0.0001). In participants with gout, SU above therapeutic target levels (≥0.36 mmol/L) were present in 10/12 (83%) at baseline and 4/12 (33%) 1 year after surgery (p=0.031). Conclusions: Clinically relevant reductions in SU occur following bariatric surgery in people with diabetes and WHO class II or higher obesity.